Contrasting Gymnosperm Diversity Across an Elevation Gradient in the Ecoregion of China: The Role of Temperature and Productivity - Pandey, Bikram; Pan, Kaiwen; Dakhil, Mohammed A.; Liao, Ziyan; Timilsina, Arbindra; Khanal, Manita; Zhang, Lin (Frontiers in Ecology and Evolution, 2021)
The species richness - climate relationship is a significant concept in determining the richness patterns and predicting the cause of its distribution. Distribution range of species and climatic variables along elevation have been used in evaluating the elevational diversity gradients (EDG). However, the species richness of gymnosperms along elevation and its driving factors in large geographic areas are still unknown. Here, we aimed at evaluating the EDG of gymnosperms in the ecoregions of China. We divided the geographical region of China into 34 ecoregions and determine the richness pattern of gymnosperms taxa along elevation gradients. We demonstrated the richness patterns of 237 (219 threatened, 112 endemic, 189 trees, and 48 shrubs) gymnosperms taxa, roughly distributed between 0 and 5300m (above sea level) in China. As possible determinants of richness patterns, annual mean temperature (TEMP), annual precipitation (PPT), potential evapotranspiration (PET), net primary productivity (SNPP), aridity index (AI), temperature seasonality (TS), and precipitation seasonality (PS) are the major predictor variables driving the EDG in plants. We used the species interpolation method to determine the species richness at each elevation band. To evaluate the richness pattern of gymnosperms in an ecoregion, generalized additive model and structural equation modeling were performed. The ecoregions in the southern part of China are rich in gymnosperms species, where three distinct richness pattern - (i) hump-shaped, (ii) monotonic increase, and (iii) monotonic decline were noticed in China. All climatic variables have a significant effect on the richness pattern of gymnosperms; however, TEMP, SNPP, TS and PS explained the highest deviance in diversity rich ecoregions of China. Our results suggests that the highest number of gymnosperms species were found in southwestern and Taiwan region of China distributed at 1600 and 2800 m elevation band. These regions could be under severe stress in the near future due to expected change in precipitation pattern and increase of temperature due to climate change. Thus, our study provided evidence of species – climate relationship that can support the understanding of future conservation planning of gymnosperms.